HAM dan Demokrasi dalam Dunia Islam - Zuman Malaka (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2009)
After the end of the Cold War, the global issue has shifted from communism and the contestation of West and East to new issue; human rights. The majority of the western countries considers Muslim world as the major violator of human rights, especially when Islamic law is concerned. As the impact, the opinion that there are abundant human rights violations in Islamic law emerges. However, this is not true, in theory or in practice. In theory, the dictums and stipulations of Islamic law contain values, rationales, aims, objectives, and effectiveness of penalty. In practice, Muslim world have own way in upholding rule of law in a sense that even if it is different from its western counterpart, it essentially has identical aims; the upholding of human rights.